Comparative Lipidomics Profiling of Acylglycerol from Tuna Oil Selectively Hydrolyzed by Thermomyces Lanuginosus Lipase and Candida Antarctica Lipase A - Junyong Xuan; Zefu Wang; Qiuyu Xia; Tingyu Luo; Qingya Mao; Qinxiu Sun; Zongyuan Han; Yang Liu; Shuai Wei; Shucheng Liu (Foods, 2022)
Lipase hydrolysis is an effective method to develop different functional types of lipids. In this study, tuna oil was partially hydrolyzed at 30% and 60% by Thermomyces lanuginosus lipase (TL 100 L) and Candida Antarctica lipase A (ADL), respectively, to obtain lipid-modified acylglycerols. The lipidomic profiling of the acylglycerols was investigated by UPLC-Q-TOF-MS and GC–MS to clarify the lipid modification effect of these two lipases on tuna oil. The results showed that 247 kinds of acylglycerols and 23 kinds of fatty acids were identified in the five samples. In the ADL group, the content of triacylglycerols (TAG) and diacylglycerols (DAG) increased by 4.93% and 114.38%, respectively, with an increase in the hydrolysis degree (HD), while there was a decreasing trend in the TL 100 L group. TL 100 L had a better enrichment effect on DHA, while ADL was more inclined to enrich EPA and hydrolyze saturated fatty acids. Cluster analysis showed that the lipids obtained by the hydrolysis of TL 100 L and ADL were significantly different in the cluster analysis of TAG, DAG, and monoacylglycerols (MAG). TL 100 L has strong TAG selectivity and a strong ability to hydrolyze acylglycerols, while ADL has the potential to synthesize functional lipids containing omega-3 PUFAs, especially DAG.